Alternative splicing is a driving force that tunes metabolic adaptations to virulence traits in the dermatophyte Trichophyton rubrum - Lopes, Marcos E. Ramos; Neves-da-Rocha, João; Sanches, Pablo R.; Oliveira, Vanderci M.; Rossi, Antonio; Martinez-Rossi, Nilce M. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAlternative splicing (AS), a common process in pathogenic fungal species, is not fully understood. We hypothesized that AS is a critical regulatory mechanism that enables species to undergo continuous adaptations during interactions with challenging host environments.MethodsWe utilized the model species Trichophyton rubrum to contextualize the role of AS in fungal physiology and virulence. We performed transcriptome-wide splicing analysis to search for AS events in RNA-sequencing data of T. rubrum grown in keratin. This scenario mimicked infection in vitro and allowed us to map biologically relevant splicing events.Results and discussionOverall, the results showed that AS is recruited to regulate approximately 12.6% of the T. rubrum genome under an infection-like scenario. We extended this analysis to ex vivo infection models of T. rubrum grown on human nails and cocultured them with human HaCaT keratinocytes. We found that AS affects a wide range of cellular processes, including amino acid and carbohydrate metabolism, cell signaling, protein folding and transport, transcription, and translation. We showed that transcription factors such as PacC and Ap1 govern the major features of fungal virulence and metabolism and are controlled by the spliceosome machinery under different infection-like conditions.ConclusionsOur data indicate that mRNA isoforms originating from AS contribute to the adaptation of T. rubrum, demonstrating that AS of transcription factor genes plays a central role in fungal pathogenesis. The transcription and splicing machinery tune fungal physiology to achieve an optimal metabolic balance in virulence traits during infection.